Laura Dolfi, Un paese sognato: la Spagna di Vittorio Bodini - Manuel Carrera Díaz (Cuadernos AISPI, 2023)
Laura Dolfi, Un paese sognato: la Spagna di Vittorio Bodini, Nardò (LE), Besa Muci Editore, 2021, 355 pp. ISBN 9788836292349